Genomic evolution of porcine reproductive and respiratory syndrome virus (PRRSV) isolates revealed by deep sequencing. - Manreetpal Singh Brar; Mang Shi; Raymond Kin-Hi Hui; Frederick Chi-Ching Leung (PLoS ONE)
Most studies on PRRSV evolution have been limited to a particular region of the viral genome. A thorough genome-wide understanding of the impact of different mechanisms on shaping PRRSV genetic diversity is still lacking. To this end, deep sequencing was used to obtain genomic sequences of a diverse set of 16 isolates from a region of Hong Kong with a complex PRRSV epidemiological record. Genome assemblies and phylogenetic typing indicated the co-circulation of strains of both genotypes (type 1 and type 2) with varying Nsp2 deletion patterns and distinct evolutionary lineages ("High Fever"-like and local endemic type). Recombination analyses revealed genomic breakpoints in structural and non-structural regions of genomes of both genotypes with evidence of many recombination events originating from common ancestors. Additionally, the high fold of coverage per nucleotide allowed the characterization of minor variants arising from the quasispecies of each strain. Overall, 0.56-2.83% of sites were found to be polymorphic with respect to cognate consensus genomes. The distribution of minor variants across each genome was not uniform indicating the influence of selective forces. Proportion of variants capable of causing an amino acid change in their respective codons ranged between 25-67% with many predicted to be non-deleterious. Low frequency deletion variants were also detected providing one possible mechanism for their sudden emergence as cited in previous reports.